Design Web Dashboard Monitoring Plant Factory Experimental Garden Faculty Of Agriculture, Udayana University - Suartama, Putu Dandy; Amrita, Anak Agung Ngurah; Khrisne, Duman Care (Politeknik Siber Cerdika Internasional, 2023)
Information technology is now always experiencing a rapid increase in its use, one example is the website. Website is a collection of web pages, summarized in a domain, which is located in the World Wide Web (WWW) on the internet. This information media is useful in various fields, one of which is in agriculture. Where the information provided can help farmers in providing better results. One of the problems in agriculture that can be seen is related to the tropical climate in Indonesia. This greatly affects environmental conditions and can cause farmers to experience crop failure. One solution that can be done in this scope is with a plant factory. Where the plant factory is a technological concept that facilitates the formation of the right and good environment for plant growth, easy to control, does not require large land and is applied indoors. In its application, the plant factory still has shortcomings related to its information media. In this study, a monitoring website dashboard was designed to function as a medium of information on the plant factory. In system design, where the website is built using several components such as HTML, PHP, MySQL and Laravel Framework. To determine the performance of the system, testing is carried out with the black box method which aims to test on application details such as the appearance of the application, functions in the application, and the suitability of the function flow with the desired process then with the system usability scale (SUS) method. Where the measurement of the quality of web-based information systems, to evaluate the level of user satisfaction with the system services.